2020
DOI: 10.1177/0886260520967149
|View full text |Cite
|
Sign up to set email alerts
|

Campus Sexual Violence Victims with Disabilities: Disclosure and Help Seeking

Abstract: Undergraduate students with disabilities represent an important population on college campuses. Yet the incidence of sexual violence and disclosing/reporting of sexual violence among this population is understudied. This exploratory and largely descriptive study uses an intersectional framework to understand the sexual victimization of undergraduate students with disabilities at a large Mid-Atlantic academic institution. The sample consisted of students who completed a sexual violence module ( N = 2,929) as pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…For those with a minoritized sexual identity, students with a disability had less favorable perceptions of anticipated peer support for survivors when compared to their peers without a disability. Disability status is not commonly examined as a demographic covariate in studies investigating sexual violence, yet research demonstrates that students with disabilities experience higher rates of sexual violence (Kirkner et al, 2022;Théorêt et al, 2022). The findings in the current study may be partially explained by research that finds students with disabilities who also had a minoritized sexual identity experienced higher rates of peer victimization during childhood compared to those who did not have a minoritized sexual identity (Lund & Ross, 2021) perhaps creating an expectation for these students about how their peers would react to students who are different than themselves-including sexual violence survivors.…”
Section: Resultsmentioning
confidence: 99%
“…For those with a minoritized sexual identity, students with a disability had less favorable perceptions of anticipated peer support for survivors when compared to their peers without a disability. Disability status is not commonly examined as a demographic covariate in studies investigating sexual violence, yet research demonstrates that students with disabilities experience higher rates of sexual violence (Kirkner et al, 2022;Théorêt et al, 2022). The findings in the current study may be partially explained by research that finds students with disabilities who also had a minoritized sexual identity experienced higher rates of peer victimization during childhood compared to those who did not have a minoritized sexual identity (Lund & Ross, 2021) perhaps creating an expectation for these students about how their peers would react to students who are different than themselves-including sexual violence survivors.…”
Section: Resultsmentioning
confidence: 99%
“…Future work may also seek to understand the intersection of survivor and mandated reporter identity, structural oppression, and mandatory reporting policy. For example, research suggests that undergraduates with disabilities may be more likely to reach out to formal campus supports following sexual violence victimization (Kirkner et al., 2020), but research investigating the experience of disabled student survivors is lacking. A recent systematic review highlighted different disclosure experiences across populations, with Black and Hispanic survivors receiving more negative reactions when disclosing to others (Ullman, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In response to the literature suggesting that students from racial, ethnic, gender, and sexual minority populations as well as students with disabilities are disproportionately burdened by SVSH [ 8 - 12 ], we will analyze IDI and FGD data from students, staff, and faculty to discern the needs and preferences regarding SVSH prevention and response among both the general population and historically marginalized groups. We explore unique cultural and contextual configurations that emerge in conversations about SVSH in these populations.…”
Section: Methodsmentioning
confidence: 99%
“…A study at a Hispanic-serving institution found that sexual and gender minority undergraduate students who experienced past-year violence were more than twice as likely to report some type of interference with their academic lives (eg, obtaining poor grades and missing class or work) compared with heterosexual, cisgender students who experienced past-year violence [ 9 ]. Studies have consistently found that violence is perpetrated at higher rates against students with (vs without) disabilities both during [ 10 - 12 ] and before enrolling in college or university [ 12 ]. This body of research highlights the need for culturally, racially, socially, and gender-relevant services for survivors of sexual and relationship violence.…”
Section: Introductionmentioning
confidence: 99%